A Constellation Model for Mentoring Undergraduates During COVID-19 - Vandermaas-Peeler, Maureen; Moore, Jessie; Allocco, Amy (Teaching and Learning Inquiry, 2023)
Conceptualizing mentoring beyond a traditional one-to-one mentor-mentee model, we utilized a constellation framework with collaborative co-mentoring among faculty, staff, near-peers, and community partners. We conducted a multi-method study to examine faculty, staff, and students’ perceptions of mentoring relationships, and we focus in this article on participants’ perceptions of how the global pandemic changed their mentoring relationships. Analyses of the study’s surveys and interviews yielded four primary themes: 1) scaffolded, developmental programming and a diverse set of mentors in an interconnected constellation positively impacts students’ and mentors’ experiences during unexpected challenges like a pandemic; 2) skilled mentoring requires a dynamic, individualized balance of instrumental, psychosocial, and reciprocal mentoring practices, taking into account unique aspects of students’ identities; 3) reduction of in-person relational mentoring was associated with significant challenges, but occasionally offset by opportunities; and 4) gaps exist in the campus ecosystem, especially for students with minoritized identities and students who are not participants in cohorted programs. A case study of a multi-year, experientially rich, and academically rigorous program highlights the potential of collaborative, interconnected, globally oriented mentoring constellations to support students’ personal, academic, and professional development, particularly when mentors were agile and adapted to new contexts. Challenges incurred in implementing a constellation model for undergraduate mentoring included scalability and capacity, particularly during the pandemic and when forming new relationships. Click here to read the corresponding ISSOTL blog post.